Flow assessment as a function of pump timing of tubular pulsatile pump for use as a ventricular assist device in a left heart simulator. Issue 7 (18th February 2022) - Sharifi, Alireza; Bark, David
Abstract: Introduction: Although mechanical circulatory support saved many lives during the last decade, clinical observations have shown that the continuous flow pumps are associated with a much higher incidence of gastrointestinal bleeding and kidney problems, among others, compared with the earlier generation pulsatile pumps. However, the presence of several moving mechanical components made pulsatile pumps less durable, bulky, and prone to malfunction, ultimately leading to bias in favor of continuous flow designs. Objective: The aim of the current work is to create a prototype tubular pulsatile pump and to test the timing of the pump in a left heart simulator. Methods: A left heart simulator to mimic pumping from a failing heart was created. This was used to experimentally test the output of a prototype ventricular assist device relative to a failing heart in the form of flow and pressure. The effect of pulsation timing was quantified. Results: A failing heart was simulated with an average flow rate of 1.1 L/min and a systolic pressure of 47 mm Hg. With the pump, the flow rate increases to 4.8 L/min and a systolic pressure of 110 mm Hg, in a copulsation mode, while activating for 300–400 ms. If the activation time is reduced, or increased, the pump becomes less effective. Load on the heart is reduced when the pump operates in a counterpulsation mode. Conclusion: A pulsatile pump, like the one proposed, provides adequate output for mechanical circulatory support, while minimizing the number of moving parts that could otherwise lead to tribological wear. Abstract : A tubular pulsatile pump was experimentally characterized in a simulated failing left ventricle. The effect of pulsation timing on flow and pressure was quantified. The proposed design provides adequate output for mechanical circulatory support, while minimizing the number of moving parts that could otherwise lead to tribological wear.